2016
DOI: 10.1021/acs.jpcc.6b05043
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Optical, and Electronic Consequences of Coexisting Crystal Orientations in β-Copper Phthalocyanine Thin Films

Abstract: The crystal structure of the β phase of copper phthalocyanine (CuPc) is a monoclinic herringbone, which is commonly created in thin films by either thermal annealing of α-CuPc at ∼300 °C or deposition on heated substrates. Of the several known CuPc crystal polymorphs, the β phase is of particular interest due to its thermodynamic stability. We observe three coexisting crystal orientations for thin films of β-CuPc to be (101), (1̅05), and (5̅02) using grazing incidence wide-angle X-ray scattering. Each of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…FTIR and Raman spectra of CuPc have been extensively explored to determine the orientation of thin films and the polymorphic transitions [22][23][24]. UV-VIS spectrum has been proved to be suitable to study the crystal structures of CuPc, especially as shown in the recent report of Microscopic UV-VIS absorption measurements [25].…”
Section: Vibrational and Optical Properties Of Cupc Crystalsmentioning
confidence: 99%
“…FTIR and Raman spectra of CuPc have been extensively explored to determine the orientation of thin films and the polymorphic transitions [22][23][24]. UV-VIS spectrum has been proved to be suitable to study the crystal structures of CuPc, especially as shown in the recent report of Microscopic UV-VIS absorption measurements [25].…”
Section: Vibrational and Optical Properties Of Cupc Crystalsmentioning
confidence: 99%
“…With exposure to FBBB(B) there are negligible changes to the UV–vis absorbance spectra of the unsubstituted Pcs (Figure S4, Supporting Information) but, following addition of THC, CoPc has a sharp increase in the intensity of its second Q band at 683 nm, suggesting coordination of the FBBB(B) + THC conjugate to the central cobalt, in addition to an increase in relative number of β‐crystallites. [ 46,56 ] Upon exposure to both FBBB(B) and THC, CuPc also has an increase in its second Q band (695 nm), albeit much lower in relative intensity to that of CoPc, further suggesting the absorbance peak intensity shifts are a result of strong FBBB(B) + THC conjugate interactions. In our previous work, [ 13 ] H 2 Pc was found to uniquely coordinate with the FBBB(B) + THC conjugate in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Though highly crystalline, the β-form is generally poorer performing or non-semiconducting in OTFTs, with mobilities on the order of 10 −5 cm 2 V −1 s −1 due to the increased face to face orientation of the Pcs. [45,46] H 2 Pc and F 16 -CuPc undergo rapid changes, gaining peak intensity within the first 10 min treatment, and continuing to gain peak intensity at each time point, becoming highly α-crystalline after 24 h of exposure to toluene vapor. While no phase angle shift occurs in the XRD spectra, large micrometer scale crystals are again observed in what were previously featureless films.…”
Section: Thin-film Characterizationmentioning
confidence: 99%
See 2 more Smart Citations